Hydrotropic Solubilization in Spectrophotometric Analysis of Cefixime in Solid Dosage Form - MAHESHWARI, R.K.; DUBEY, NIDHI; DUBEY, NITIN; SINGH, MAHAVEER (Asian Journal of Chemistry, 2010)
Various techniques are employed to enhance the aqueous solubility of poorly water-soluble drugs and hydrotropic solubilization is one of them. In the present investigation, cefixime has been selected as a poorly water-soluble model drug. There were more than 120 and 240 fold enhancements in aqueous solubility of cefixime by 8 M potassium acetate and 6 M ammonium acetate solutions, respectively as compared to aqueous solubility. These hydrotropic agents were employed to solubilize the drug from the fine powder of tablet formulations. The selected λmax for spectrophotometric estimation was 288 nm. The hydrotropic agents and the additives used in the manufacturing of tablets did not interfere in the analysis.